A joyful play of architecture; exploring inviting atmospheres and interactive spaces a new culture centre and school in Ängelholm - Olsson, Minna (My University, 2025)
In today´s cities there´s a need for public buildings where people can feel welcomed, especially after the pandemic. Designing for a large audience can be somewhat challenging as one needs to consider the experience of space from the perspective of many different people. Another challenge is maintaining a welcoming atmosphere and transparency in a large scale building. This master´s thesis has explored how the design of a building can create an inviting atmosphere that makes the visitors curious to explore its functions and still house a large program. The result of the thesis has been shown through a new culture center and school in the city of Ängelholm where, on a detailed level, the aim has been to, through design, enhance the inviting atmosphere and inspire to creative and cultural participation. The method was divided into a theoretical and practical part, where the theoretical part foremost focused on the analysis of built references. Other tools that have been used are model making, interviews, literature, study trips, sketching, renderings and drawings.The methods and tools were used in an iterative process, with the aim to continously improve the final design. Through wooden elements and cantilevering parts, the new culture center and school showcased a building that greets its visitors from many directions. The curved cantilevering parts created spaces for exterior meetings as well as acted as a doorstep to enter the building. Interiorly the building invited for visitors to sit down inbetween the pillars or to further walk up towards the curved interior and enjoy the framing of nature in different angles. From the result it was concluded that certain design gestures and a care for the human centric experience are all important factors whilst designing inviting spaces. Working with even the smallest details also has important meaning as the details sets the tone for the atmosphere as a whole. These inviting elements were amongst others, the niches between the pillars and beams, the proportions of warm materials and the care for window sills and placement, which all contributed to a joyful play of architecture.
Keywords: public building, inviting atmospheres, culture centre, culture school, creative spaces, curiosity, Ängelholm